Hypoxia-related mechanisms inducing acute mountain sickness and migraine - Frank, Florian; Kaltseis, Katharina; Filippi, Vera; Broessner, Gregor (Frontiers in Physiology, 2022)
Experimental models of human diseases are vital for pathophysiological and therapeutic research. To investigate the initiation, maintenance, pathophysiology and even termination of a migraine/headache attack these models are urgently needed. Results from different studies promote the profound involvement of hypoxia in migraine and other primary/secondary headaches. The possible mechanisms that drive the induction of headaches through hypoxia are still unknown, but several modes of action, such as increased blood flow, dilation of cerebral arteries, the release of nitroglycerin, calcitonin gene-related peptide and adenosine or increased oxygen extraction are discussed intensively. In studies exposing healthy volunteers and people with a history of migraine to controlled normobaric hypoxia, our research group could demonstrate normobaric hypoxia to be an effective trigger of migraine headaches. Furthermore, a longitudinal measurement of calcitonin gene-related peptide (CGRP), during a hypoxic challenge in migraine patients, revealed increasing CGRP levels with prolonged hypoxic challenge. Since GRP has been linked to migraine and other headache disorders, hypoxia could be regarded as initiator for headaches on a neurotransmitter basis. Furthermore, it has been known for more than two decades from studies in vitro and in vivo that hypoxia can induce cortical spreading depression, a phenomenon believed to represent aura. Considering the increased prevalence of migraine in altitude populations and the solid pathophysiological changes on cellular and neurotransmitter level – the role of hypoxia should be investigated in greater detail by the headache community. Controlled normbaric hypoxia, using a hypoxic chamber, enables to study migraine/headache pathophysiology under highly standardized conditions without the side effects of a pharmacological intervention.